The strength, fracture, and fatigue of materials. / Translated by Shigeru Matsuo and Michiko Inoue. Edited by John D.C. Crisp. - Yokobori, Takeo,1917-
Stamped on t.p.: Stechert-Hafner Service Agency, inc., New York.